Biomarker of buccal mucosa cells damaged after exposure to panoramic radiography: a literature review - Dwi Putri Wulansari; Azhari Azhari (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: This review aimed to understand the effect of exposure to panoramic radiographs on exfoliated buccal mucosal cells at the cellular level. Review: The dose of radiation exposure in dentistry, both intraoral and extraoral, has been regulated by The National Radiological Protection Board (NRPB). However, even though it is given in small doses, x-ray radiation due to intraoral and extraoral radiographs still has a radiobiological effect on the exposed tissue. The radiobiological effects of X-ray exposure can cause changes in biological molecules, either directly or indirectly, within hours or days. There are two classification of this radiobiological effect, called deterministic and stochastic effect. The deterministic effect occurs when the dose given exceeds the recommended dose by the NRPB, whereas the stochastic effect does not have any threshold that needs to be exceeded to give some adverse impact to the exposed tissue One method used as a predictor or biomarker of genetic damage due to exposure to physical or chemical mutagenic agents in humans is micronucleus (MN). The biomarker for the cell damaged is the change of nucleus shape and outline, called pycnosis, karyolysis, karyorrhexis. Conclusion: The exposed to x-ray from panoramic could induce cell and genetic damaged. Prescription for panoramic radiographic examination in patients should be as effectively as possible according to the principles of ALADA (as low as diagnostically acceptable) to avoid adverse effects on the exposed tissue.